2007
DOI: 10.1177/1475921707082309
|View full text |Cite
|
Sign up to set email alerts
|

Higher Order Spectra for Crack and Misalignment Identification in the Shaft of a Rotating Machine

Abstract: Higher order spectra (HOS) are the tools in signal processing for the identification of the presence of higher harmonics in a signal which is a typical case of a non-linear dynamic behavior in mechanical systems. The breathing of a crack during shaft rotation also exhibits a non-linear behavior. The crack is known to generate 2X (twice the machine RPM) and higher harmonics in addition to 1X component in the shaft response during its rotation. Misaligned shaft also shows such feature as a crack in a shaft. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…For instance, Hameed et al [38] provided a comprehensive review of CM techniques for wind turbines, where it was shown that accurate information on the overall condition of the rotor (a very important component of the wind energy converter) can be obtained by trending the relation between wind speed and active power output of the wind energy converter (WEC). The study [38] also showed that the use of higher order signal processing tools (bispectrum and bicoherence) [18][19][20][21][22] for detecting the presence or absence of phase coupling between the frequency components of the electrical power signal when classifying the WEC as faulty or healthy is very possible.…”
Section: Overview Of Data Fusion For Faults Detection and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Hameed et al [38] provided a comprehensive review of CM techniques for wind turbines, where it was shown that accurate information on the overall condition of the rotor (a very important component of the wind energy converter) can be obtained by trending the relation between wind speed and active power output of the wind energy converter (WEC). The study [38] also showed that the use of higher order signal processing tools (bispectrum and bicoherence) [18][19][20][21][22] for detecting the presence or absence of phase coupling between the frequency components of the electrical power signal when classifying the WEC as faulty or healthy is very possible.…”
Section: Overview Of Data Fusion For Faults Detection and Classificationmentioning
confidence: 99%
“…This integration of multiple VCM approaches sometimes complicates the entire fault finding process. Efforts aimed at overcoming these deficiencies have led to the application of higher order spectra (HOS) [18][19][20][21][22], where both amplitude and phase information are retained. Other researchers have also attempted to standardise rotating machines fault diagnosis by incorporating artificial intelligence (AI) techniques such as artificial neural networks (ANN) [23][24][25] and support vector machines (SVM) [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Sinha [9] showed experimentally that higher order spectra analyses (bispectrum and trispectrum) can be used to distinguish malfunctions usually found in rotating machines, namely, crack and misalignment. The identification of higher harmonics in the system vibration responses is a typical case of nonlinear behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The bispectrum (and the bicoherence) was applied by Boltežar et al [28] to the dynamics of washing machines, demonstrating that certain excited modes of the oscillation could be associated with quadratic phase coupling. It has been demonstrated experimentally that the bispectrum can be used to monitor the increase in second harmonic generation by a rotating axle which is cracked or misaligned [29].…”
Section: Introductionmentioning
confidence: 99%
“…From Eqs (28). and(29) odd powers of the noise have a zero expected value and utilizing the integral[35] +∞ −∞…”
mentioning
confidence: 99%